Residual Perforation Risk Assessment of Intratympanic Steroids via Tympanostomy Tube Versus Transtympanic Injections. (18th May 2021) - Simani, Liam; Shilo, Shahaf; Oron, Yahav; Eta, Rani A.; Handzel, Ophir; Muhanna, Nidal; Warshavsky, Anton; Horowitz, Gilad; Ungar, Omer J.
Abstract : Objectives/Hypothesis: To investigate the risk of residual tympanic membrane (TM) perforation after intratympanic (IT) steroidal treatment administered via transtympanic injection compared with trans‐tympanostomy tube (TyT). Study Design: Case series, systematic review and meta analysis. Methods: Data were retrieved from the medical files of an original cohort of all consecutive patients with sudden sensorineural hearing loss necessitating IT steroidal treatment in a tertiary medical center between January 1, 2016 and November 20, 2020. A systematic literature search of "MEDLINE" via "PubMed, " "Embase, " and "Web of Science" on comparable published cases was performed and meta‐analysis was established. Results: Eighteen studies describing 818 ears were included in the quantitative meta‐analysis in addition to a local cohort of 140 ears. The proportion of residual TM perforation was 1.11% and 1.14% (95% confidence interval: 0.01%–3.27% and 0.028%–2.38%) in the TyT and trans‐tympanic groups, respectively, suggesting no significant difference in residual TM perforation risk between these techniques. Conclusion: IT steroid therapy via trans‐TyT is not associated with more residual perforations than IT steroid therapy via transtympanic injections. Level of Evidence: NA Laryngoscope, 131:E2583–E2591, 2021